Evaluating the Impact of Geoeducation Programs on Student Learning and Geoheritage Awareness in Greece - George Zafeiropoulos; Hara Drinia (Geosciences)
In recent years, multiple efforts to promote geoscience and geoenvironmental awareness have highlighted the need for geoeducation. This article explores the importance of integrating geoeducation into the Greek curriculum for promoting a deeper understanding of geosciences. The method used is primarily based on a mixed-methods approach, covering both qualitative and quantitative data. A preliminary assessment revealed a lack of information on the conceptual framework of geosites and geoparks. Following this, a geoeducation tool was developed to introduce the basic principles of geoeducation. The evaluation showed a significant increase in understanding and a heightened desire for further knowledge on geoeducational topics. To address current deficiencies, effective integration of this geoeducational tool requires comprehensive teacher training and curriculum reform. Promoting geoeducation through school programs is critical for creating a more informed, responsible, and sustainable society. This paper advocates policy changes and educational initiatives to firmly integrate geoeducation into the Greek educational system.